Doxycycline-induced exogenous Bmi-1 expression enhances tumor formation in a murine model of oral squamous cell carcinoma. Issue 5 (3rd May 2020) - Kalish, Jocelin M.; Tang, Xiao-Han; Scognamiglio, Theresa; Zhang, Tuo; Gudas, Lorraine J.
ABSTRACT: B Cell-Specific Moloney Murine Leukemia Virus Integration Site 1 (Bmi-1, Bmi1), an epigenetic protein, is necessary for normal stem cell self-renewal in adult animals and for cancer stem cell (CSC) functions in adult animals. To elucidate the functions of Bmi-1 in the oral cavity we created a transgenic mouse line (KrTBmi-1) that expresses ectopic, Flag-tagged Bmi-1 in tongue basal epithelial stem cells only upon doxycycline (DOX) treatment. Genome wide transcriptomics and Ingenuity Pathway Analysis identified several pathways altered by exogenous Bmi-1 expression in the normal tongue epithelium, including EIF2 signaling ( P value = 1.58 x 10 −49 ), mTOR signaling ( P value = 2.45 x 10 −12 ), oxidative phosphorylation ( P = 6.61 x 10 −3 ) and glutathione redox reactions I ( P = 1.74 x 10 −2 ). Overall, our data indicate that ectopic Bmi-1 expression has an impact on normal tongue epithelial homeostasis. We then assessed the KrTBmi-1 mice in the 4-nitroquinoline 1-oxide (4-NQO) model of oral carcinogenesis. We found that 80% of mice expressing exogenous Bmi-1 (+DOX, +4-NQO KrTBmi-1; N = 10) developed tumors classified as grade 3 or higher, compared to 60% and 40% of mice expressing just endogenous Bmi-1 (+DOX, +4-NQO Kr and -DOX, +4-NQO KrTBmi-1 groups, respectively; N = 10/group; P value = <0.0001); and 30% of mice expressing ectopic Bmi-1 mice developed 20 or more lesions compared to 10% of mice expressing only endogenous Bmi-1 ( P = .009). This demonstrates that exogenous Bmi-1 expression increases the susceptibility of mice to 4-NQO-induced oral carcinogenesis, strengthening the evidence for Bmi-1 as a therapeutic target in human oral squamous cell carcinoma.